What do professionals experienced in delivering end-of-life care want to know about advance care planning (ACP)?. Issue 1 (1st June 2011) - Poultney, J; Munday, D; Maclaran, S; Martin, S
Abstract : West Midlands South HIEC ACP project aims to encourage the use of advance care planning (ACP) more widely by training and supporting a multidisciplinary group of health care professionals from local acute trusts, community services and hospices who provide care for patients at the end of life. The project includes a study day focusing on definitions of ACP, ethical and legal implications, use of local documentation and communication skills training – exploring approaches to initiating ACP conversations with patients using role play with actors. To date 40 professionals have received training with a further 40 scheduled for March and April 2011. Those attended included: palliative care and long term condition clinical nurse specialists, district nurses, care home staff, occupational therapists, physiotherapists and an elderly care physician. At the start of the day all of the group are asked to write down three questions that they want to have answered. Questions have fallen into five main categories: ethical and legal aspects (34%), use of documentation (30%), when to do ACP (19%), how to have the conversation (11%) and other (6%). Over the course of the day we ensure that all questions are addressed. All participants have been asked to complete an online questionnaire 3 months after the training to assess its effectiveness. Using questions in this way has provided a focus for the course, helping to identify where knowledge gaps and potential barriers to ACP lie.